Factors determining the hatching success of Antarctic krill Euphausia superba embryo: lipid and fatty acid composition - Yoshida, T; Patti Virtue; Kawaguchi, S; Peter Nichols (2011)
The present study addresses the effect of maternal diet on hatching success and condition of embryos and larvae of Antarctic krill Euphausia superba. Lipid and fatty acid content and composition were determined in field and laboratory samples. Developmental stages analyzed in embryos included: multiple-cell, gastrula, and limb-bud stages. Larval stages analyzed included: nauplius I, nauplius II, and metanauplius. Laboratory-reared embryos were spawned by gravid females incubated under three feeding groups: (1) phytoplankton mixture, (2) phytoplankton mixture and minced clam, and (3) phytoplankton mixture,minced clam, and commercial larval food. Hatching success was highest in group 3 (100%), lowest in group 1 (0%), and highly variable in field samples (0–48%). Lipid decreased slightly in embryos during embryonic development, while large decreases in lipid were found during nauplius development. High levels of 18:2(n-6), 20:4(n-6), and 22:6(n-3) observed with group 3 samples coincided with high hatching success in krill embryos. The ratio of 22:6(n-3)/20:5(n-3) also correlated to hatching success of embryos. The fatty acid profile of embryos in group 3 was similar to that of the fieldcollected embryos, reflecting the contribution of the commercial larval food in the maternal diet. In our study, the maternal diet was found to influence the fatty acid composition of embryos and in turn affects the hatching success of krill. Specific polyunsaturated fatty acids appeared to play important roles in embryogenesis in krill.